(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the functional outcome of external fixator in children with open tibial fracture in the department of Orthopaedics Surgery of LUH Hyderabad/ Jamshoro Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Orthopaedic Department of LUMHS from June 2014 to March 2015. Materials and methods: In this study, 60 children (younger than 12 years) suﬀering from Gustilo grade II and III open fracture of tibia were admitted at the emergency department of the center and evaluated. All the cases were treated with external fixation, after complete counseling their parents or their attendants. While the children were admitted at the emergency department of the hospital, they underwent prophylaxis using antibiotic. All patients underwent washing and primary debridement operation at the emergency department. According to the attending surgeon, the patients were treated either using external fixator after hospitalization. After management union of the fracture was assessed through clinical examinations such as lack of pain, tenderness, and radiography of both lateral and anteroposterior (AP) views during the follow-up period. <>Results: In this study mean age was found 10.3+3.6 years, male were found in majority 42(80.67%). Road traffic accident was the most common cause of mechanisms of injury was in 35(67.31%). Cases with grade III type of fracture found in majority 57.69%. union after management was achieved 98.8% of the cases, superficial infection was found in 06(11.53%) cases, while deep infection, Malunion and delayed union were found 03(5.76%), 07(13.46%) and 05(9.61%) respectively. While non-union was found only in one case. Conclusion: External fixator is very safe, insignificant intrusive, get short surgical time, following by short hospital duration as well as can be applicable as unequivocal & effective administration of open fractures of tibia among children.